Gender, science, and technology : perspectives from Africa - Kitetu, Catherine Wawasi (Codesria gender series ;, 2008)
"This sixth volume of the CODESRIA Gender Series is a collection of discourses, perspectives, practices and policies on the role of the female gender in science and technology, particularly in the African context. Although widely advocated as the indisputable foundation for political and economic power in the modern world, science and technology remains marked by various layers and dimensions of gender inequality that work to the disadvantage of girls and women. Despite the fact that a lot of awareness has been created, and gender issues are now more readily acknowledged by various development initiatives in Africa, participation in science and technology still remains a hurdle as far as girls and women are concerned. A common theme that runs through the book is how feminine identities, ideologies of domesticity and gender stereotypes, and the inadequacy or lack of clear policies facilitate the invisibility of women in science and technology. This notwithstanding, women have never ceased devising clever and ingenious ways that would enable them to master nature, from the margins. The book provides a window onto the current state of female participation in science and technology in Africa, along with an analysis of the historical backgrounds, current educational and professional contexts, and prospects for the future. While it is evident that more research needs to be done, with more groups in different regions, this volume brings together a rich and inspiring collection of qualitative insights on gender, science and technology in Africa."--Book cover